Penerapan Ilmu Manajemen Bisnis Guna Pendampingan Mitra Usaha Kecil Menengah “Djamoe Sarongge” di Desa Ciputri - Iswaldi*, Ihsan; Yachya, Nadia; Dabi–Dabi, Angtoni; Wirya, Deborah Putrilla; Tjakra, Jonathan Dikke Mike; Kurnia, William; Michaela, Clarimond; Natawidjaja, Chrystian (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
This activity aims to improve the capability of running a business independently for the owner of small to medium enterprise Djamoe Sarongge. In which it produces varieties of traditional healthy drinks. The owner had problems regarding four business system: operational, marketing, human resource management, and financial. All these problems are present on the absence of education, the nonexistent entrepreneurship capability that looks forward for opportunity. In the future, this activity should be able to increase the production quantity, increase product penetration to potential customers, increasing the capability of owner to run the business, and shaping the owner to be able to financially manage the business. There are some methods used in this activity such as qualitative observation, mentoring, and field practice which those methods occur at Ciputri. This activity resulted an increase in the quality of the products from the composition to the extended shelf life, knowledge to perform offline and online selling through social media, brochures as marketing media, new packaging, knowledge to perform business and the systems, standard operating procedure for production process, and the ability to make financial report. Aside from that, the activity also produces new product line to the business. With the variation provided through the products and the added knowledge about 4 business systems, an increase in product sales as much as 70 units and market penetration throughout Ciputri area.